Endometrial preparation does not affect the risk of hypertensive disorders of pregnancy in low-risk women undergoing frozen embryo transfer. (4th March 2022) - Dallagiovanna, Chiara; Cappellari, Michela; D'Ambrosi, Francesco; Reschini, Marco; Kordas, Karina; Li Piani, Letizia; Filippi, Francesca; Somigliana, Edgardo
Abstract: Objective: Frozen embryo transfer (FET) is associated with a higher risk of hypertensive disorders in pregnancy. The objective of the present study is to evaluate the effect of different protocols of endometrial preparation on the risk of these disorders. Methods: We conducted a retrospective cohort study on 594 singleton pregnancies achieved by embryo transfer of single frozen-thawed blastocysts. Women with preexisting risk factors for hypertensive disorders were excluded. Women were divided into two groups according to the endometrial preparation protocol: either natural cycle ( n  = 495) or programming cycle with hormonal replacement therapy ( n  = 97). The primary outcome was the frequency of hypertensive disorders in pregnancy: specifically, gestational hypertension and preeclampsia. Results: No differences emerged between women following the natural cycle and those following the programming cycle in the frequency of gestational hypertension (5 vs. 4%) and preeclampsia (1.1 vs. 1.2%). No impact emerged also after multivariate analyses. Conclusions: Women receiving hormonal replacement therapy have the same risk of gestational hypertension and preeclampsia as women following natural cycles when considering low-risk singleton pregnancies.